Prospects and constraints of formal rice seed systems in Nepal - Sapkota, S; Regmi, PP; Pandey, S; Tripathi, B; Sah, SK (Agronomy Journal of Nepal, 2013)
Rice (Oryza sativa) is the main crop of Nepal. Farmers in Nepal mostly use seed from their stock in the form of informal seed systems which is around 92.3% of total seed requirements. In Nepal, formal seed of rice is distributed mostly by public institutions and very nominal amount by private seed dealers. Unavailability of quality seed of preferred variety is the key issue for rice seed systems. This study tries to attempt to address existing rice seed supply systems in Nepal thereby understanding its opportunities and constraints. The study was undertaken by collecting information from various documented sources and primary data from the household survey done at Chitwan and some seed related institutions during 2010/11. Formal and the informal are the two dimensions of the seed system for rice. Farm saved seed and farmers- to- farmers exchange of seed are informal seed system whereas private seed dealers and public institutions’ involvement in the seed sector are formal seed systems. Due to dominant of informal seed systems, there is the low seed replacement rate of 8.7% for rice. Nevertheless, breeder seed is solely produced by different Research Centers of Nepal Agriculture Research Council (NARC), whereas foundation seed is produced by NARC Research Centers and other institutes as well. This amount of source seed does not seem enough to cover rice areas of the country. To tackle problem of seed insufficiency, quality of source seed should be maintained by public institutions aside from creating awareness to farmers by service providers about the importance of producing certified seed by using foundation seed in farmers’ field. DOI: http://dx.doi.org/10.3126/ajn.v2i0.7531 Agronomy Journal of Nepal (Agron JN) Vol. 2: 2011 pp.157-167